Experience of Sutured Limbal Stem Cell Conjunctival Autograft after Pterygium Excision - Eddyanto Eddyanto; Ismi Z; Fazarrahmah Fazarrahmah; Windi IR (Majalah Oftalmologi Indonesia, 2015)
Background: To know the effectiveness of sutured limbal stem cell conjunctival autograft after pterygium excision in order to avoid recurrencies. Method: This is a prospective study of limbal stem cell conjunctival autograft after pterygium excision during December 2011 until April 2012. Type of operation were pterygium excision followed by cojunctival limbal stem cell autograft. Follow up be conducted at day 1, 1 week, 1 and 3 month post operatively. The recurrence rate was evaluated using Portable PASW statistics 18 software. Result: Twenty cases of pterygium had been operated. Ten cases could be evaluated 3 months. Three males and 7 females, average age was 50.2 Â± 10.55 year, range 38-72. 2cases were pre existing recurrence pterygium. BCVA pre operation range 1.00 - 0.1. BCVA post operation range 1.00 â€“ 0.20. One of 10 cases was recurrence after this study, the BCVA decrease and need repeated excision and limbal stem cell conjunctival autograft. There is no statistically significant correlation of the type of pterygium pre and recurrence post operatively. Moderate association was noted between BCVA pre operation and recurrence rate post operatively. Very strong association was noted between age of these patient and recurrence post operatively. There is a significantly differrence of BCVA before and after operations. Conclusion: Sutured limbal stem cell conjunctival autograft after pterygium excision in order to avoid recurrencies was effective 3 months after operation. The recurrence rate is 10%. This study need more samples and comparring group with other technique in order to know this tehnique is better than other or not. Keywords: Ocular surface disorder, corneal conjunctivalisation, pterygium excision, limbal stem cell transplantation